THE MICROFIBRILLAR STRUCTURE OF THE CELL WALLS OF THE FILAMENTOUS FUNGUS, Allomyces - Aronson, Jerome M. (The Rockefeller University Press, 1960)
Cell walls of the fungus, Allomyces, were isolated by chemical procedures, using either potassium permanganate oxidation or glacial acetic acid-hydrogen peroxide treatment followed by dilute mineral acid. The structure of the treated walls was investigated by means of electron microscopy and electron diffraction analysis which showed that rhizoidal walls were especially suitable for observation. Chitin microfibrils exist in the extreme tips of rhizoidal walls, and tend to lie in a preferred longitudinal orientation. Older rhizoidal wall segments show a crossed fibrillar structure under a thin layer of short randomly arranged microfibrils. In the possession of systems of crossed fibrils these walls are like the cell walls of certain green algae. Walls of branch rhizoidal filaments were observed in the early stages of development, in which case the observed microfibrillar orientations are such that it is possible to envisage their origin from pre-existing fibrils that have passively reoriented. With respect to the continued growth of the filaments, however, it is difficult to explain the observed microfibrillar arrangements in terms of the "multi-net" theory. Hyphal walls usually show two layers, the outer consisting of microfibrils arranged randomly, and the inner consisting of well oriented microfibrils running parallel with the longitudinal axis of the hypha. The oriented inner layer appears to be similar in structure to the secondary wall of the Phycomyces sporangiophore.